Ontological metaphors in website ads for Japanese-Language hotels in South Bali - Meidariani, Ni Wayan; Meilantari, Ni Luh Gede; Sudipa, Made Henra Dwikarmawan (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Ontological metaphor is used to conceptualize something abstract into something real. Ontological metaphors are found in sentences on hotel websites used as a form of promotion. This study has two objectives: 1) to find out the types of ontological Japanese metaphors on Japanese-language hotel websites in Bali, and 2) to explain the conceptual meaning of ontological metaphors on Japanese-language hotel websites in Bali. This study is qualitative research and takes a phenomenological approach. The research phase begins by observing the sentences on four hotel websites in South Bali. Furthermore, the data was collected using the observation method in conjunction with reading and note-taking techniques. The theory of conceptual metaphor developed by Lakoff and Johnson is used to analyze ontological metaphors. The data were analyzed using the identity method, namely explaining the conceptual meaning contained in the ontological metaphor. Ontological metaphors on hotel websites emphasize service and luxury. Services and luxuries as something abstract are visualized as things that can be felt and enjoyed by humans, therefore creating a metaphorical expression in the form of "enjoy the luxury" (zeitaku o sashimi kudasai). The results of the study show that there are four conceptualizations of ontological metaphors on Japanese-language hotel websites in Bali, namely: 1) stress or fatigue is something that can be eliminated; 2) service is something that can be felt; 3) luxury is something that can be enjoyed; and 4) memories are something luxurious. Children's language politeness and the role of parents in supervising and educating children on this platform are very important.